Trend Strategy to Prevent Bullying in Islamic Boarding Schools (Pesantren) - Arif, Muhamad; Abd Aziz, Mohd Kasturi Nor; Abdurakhmonovich, Yuldashev Azim (SCAD Independent, 2024)
The presence of bullying within Islamic boarding schools is a serious issue that demands immediate attention and prevention. This research aimed to investigate the factors of bullying, the characteristics of bullying behavior in Islamic boarding schools, and the preventative measures implemented by Islamic boarding schools to shield their students. The research approach employed is a systematic literature review focused on published articles. The data was restricted to articles published from 2013 to 2023. The researchers used PRISMA analysis to analyze the data. The research results found that individual, a supportive environment, parental parenting patterns, particularly authoritarian parenting patterns, and aggressive or violent video or film elements were all factors in bullying. Several strategies had been put into effect, including the following: creating a fun cottage movement (GPM) program, strengthening conflict and emotional management, carrying out regular outreach and training regarding the dangers of bullying, cyber bullying, and legal education for bullies, implementing an anti-bullying curriculum, and others. Besides, more comprehensive research findings indicated that Islamic boarding schools must implement character formation based on Josephson’s “Character Counts” theory with six main pillars to prevent bullying behavior among students.